Entinostat reverses cisplatin resistance in esophageal squamous cell carcinoma via down-regulation of multidrug resistance gene 1. (1st February 2018) - Huang, Xiao-Ping; Li, Xuan; Situ, Min-Yi; Huang, Li-Yun; Wang, Jun-Ye; He, Tian-Cheng; Yan, Qi-Hang; Xie, Xiu-Ying; Zhang, Yu-Jing; Gao, Yuan-Hong; Li, Yu-Hong; Rong, Tie-Hua; et al.
Abstract: Cisplatin resistance frequently occurs in esophageal squamous cell carcinoma (ESCC). The underlying mechanism for cisplatin resistance in ESCC remains largely obscure. Here we report that entinostat reversed cisplatin resistance in ESCC both in vitro and in vivo by induction of apoptosis and inhibition of cell proliferation, accompanied by a decrease of multidrug resistance gene 1 (MDR1), P-Src, Mcl-1, Cyclin D1 and an increase of cleaved PARP. MDR1 expression was associated with worsen survival of ESCC patients with cisplatin-based chemotherapy. Dasatinib potentiated entinostat to overcome cisplatin resistance. By inhibiting Src, dasatinib reduced the expression of MDR1 and Mcl-1. Furthermore, Obatoclax, an inhibitor of Mcl-1, obviously decreased the expression of MDR1, suggesting that entinostat might surmount cisplatin resistance in ESCC via a Src-Mcl-1-MDR1 pathway. Interestingly, cisplatin also enhanced the effect of entinostat both in vitro and in vivo. Our data disclose a molecular basis that entinostat reverses cisplatin resistance, and provide a promising strategy with combinatorial drugs to treat cisplatin resistant ESCC patients. Highlights: Entinostat reverses cisplatin resistance in ESCC both in vitro and in vivo. Entinostat overcomes cisplatin resistance via Src-Mcl-1-MDR1 pathway. MDR1 predicts worsen survival of ESCC patients. Dasatinib potentiates entinostat to surmount cisplatin resistance.